2016
DOI: 10.3343/alm.2016.36.1.28
|View full text |Cite
|
Sign up to set email alerts
|

Basophil Markers for Identification and Activation in the Indirect Basophil Activation Test by Flow Cytometry for Diagnosis of Autoimmune Urticaria

Abstract: BackgroundThe indirect basophil activation test using flow cytometry is a promising tool for autoimmune urticaria diagnosis. We aimed to identify better donor basophils (from atopic vs. non-atopic donors and interleukin-3 primed vs. unprimed basophils) and improve basophil identification and activation markers (eotaxin CC chemokine receptor-3 [CCR3] vs. CD123 and CD63 vs. CD203c).MethodsDonor basophils were obtained from non-atopic and atopic group O donors. Positive control sera were artificially prepared to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 25 publications
1
22
0
3
Order By: Relevance
“…BATs assess histamine release or upregulation of activation markers of donor basophils in response to stimulation with the serum of CSU patients. BATs can help to co‐assess disease activity in patients with urticaria as well as to diagnose autoimmune urticaria . Furthermore, BAT can be used as a marker for responsiveness to ciclosporin A or omalizumab …”
Section: Diagnosis Of Urticariamentioning
confidence: 99%
“…BATs assess histamine release or upregulation of activation markers of donor basophils in response to stimulation with the serum of CSU patients. BATs can help to co‐assess disease activity in patients with urticaria as well as to diagnose autoimmune urticaria . Furthermore, BAT can be used as a marker for responsiveness to ciclosporin A or omalizumab …”
Section: Diagnosis Of Urticariamentioning
confidence: 99%
“…If CD123 is really down-regulated by activation, it would be very interesting to assess if a gating strategy using CCR3 (CD193), the eotaxin receptor, might bear the same concern reported by others elsewhere [3,4], as CCR3 appears to be down-regulated upon basophil activation [2,14,15]. Interestingly, some authors reported a paper where a phenotyping protocol using a combination of CD123 and CCR3 markers, improved significantly the performance of BAT, respect to the only CD123 [16].…”
Section: Discussionmentioning
confidence: 90%
“…shows the best performance to identify basophils. 24 After gating on CD45 moderately positive and low SSC cells, CD123 associated with HLA-DR seems to be a robust combination to identify basophils that are strongly positive for the first marker and negative for the second one. Moreover, this combination permits to separate basophils from plasmacytoid dendritic cells, which express bright HLA-DR. Basophils can be segregated from myeloblasts by the negativity of immaturity markers (CD34-HLA-DR-CD117-); however, CD38 is strongly positive in basophils.…”
Section: Flow Cytometrymentioning
confidence: 96%